A case report of a patient with first phenotype of papillary thyroid carcinoma and heterochronous multiprimary tumor harboring germline MUTYH Arg19*/Gly286Glu mutations. (January 2021) - Wang, Mingbo; Zhu, Fuxin; Luo, Ningning; Han, Tiantian; Wang, Musen
Abstract: MUTYH -associated polyposis (MAP) is an autosomal recessively inherited disease with multiple system tumors mainly in alimentary system. Tumor occurrence of MAP patients is highly heterogeneous in space and time. MAP is associated with germline biallelic mutations in MUTYH . The targeted next‑generation sequencing technology and Sanger sequencing are the important methods to screen MUTYH mutations now. Herein, we identified a patient with heterochronous multiprimary tumor carring MUYTH Arg19*/Gly286Glu compound heterozygous mutations. The patient in this case had a first phenotype of thyroid cancer at age 44, which earlier 2 years than the alimentary system cancers. In conclusion, our case report creases the in-depth understanding of the MAP heterogeneous phenotype and further reminds recommendations for improvement of health management and genetic counseling, special treatment plans.